Who Is Covered and Who Underreports: An Empirical Analysis of Access to Social Insurance on the Egyptian Labor Market - Rania Roushdy; Irène Selwaness (Global Labor Organization (GLO), 2017)
This paper investigates the dynamics and determinants of having access to social insurance coverage on the Egyptian labor market among wage and non-wage workers. The paper explores two issues: the worker- and enterprise- level determinants of having access to social insurance and the risk of underreporting insurable wage to the social security authority. Using data from the Egyptian Labor Market Panel Survey for 1998 and 2006, the likelihood of having access to social insurance coverage is estimated by a probit regression model for all workers, for wage and non-wage workers, separately. Given the potential endogeneity between the type of work and social insurance access, instrumental variable technique is applied. Results show that men, older, married, better educated and white collar highly skilled workers are more likely to be socially insured. Underreporting insurable wages is negatively correlated with education and work experience. High contribution rates requested from both the employer and employee, combined with basing benefits on wages level of the last few years of service, and the weak capacity of law enforcement encourage employers and employees to either not participate in the social insurance system or contribute on amounts that are lower than their actual wage. The paper is one of the few studies that focus on the phenomenon of coverage gap and underreporting salaries to the social security administration.
Keywords: J46; H55; C36; 330; Social Security; Social Insurance; Informality; Endogeneity; Instrumental variables